2021
DOI: 10.1021/acs.langmuir.1c01589
|View full text |Cite
|
Sign up to set email alerts
|

Pinning in a Contact and Noncontact Manner: Direct Observation of a Three-Phase Contact Line Using Graphene Liquid Cells

Abstract: Pinning of a three-phase contact line at the nanoscale cannot be explained by conventional macroscale theories and thus requires an experimental insight to understand this phenomenon. We performed in-situ transmission electron microscopy observation of the three-phase contact lines of bubbles inside graphene liquid cells to experimentally investigate the causes of nanoscale pinning. In our observations, the three-phase contact line was not affected by the 0.6 nm-thick inhomogeneity of the graphene surface, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Ultra-high vacuum (UHV) conditions are integral to a wide range of characterization techniques including X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), low-energy ion scattering, and even the Large Hadron Collider due to requirements for surface cleanliness and the unimpeded transmission of electron or ion beams. Many of these techniques allow detailed surface morphology measurements or chemical composition analyses, enabling the quantitative study of thin films, interfaces, residues, and contamination for process development and control. For instance, XPS has been critical for analysis of the chemical composition of carbon nitride, graphene, , MXenes, and rare-earth oxides (REOs), among other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Ultra-high vacuum (UHV) conditions are integral to a wide range of characterization techniques including X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), low-energy ion scattering, and even the Large Hadron Collider due to requirements for surface cleanliness and the unimpeded transmission of electron or ion beams. Many of these techniques allow detailed surface morphology measurements or chemical composition analyses, enabling the quantitative study of thin films, interfaces, residues, and contamination for process development and control. For instance, XPS has been critical for analysis of the chemical composition of carbon nitride, graphene, , MXenes, and rare-earth oxides (REOs), among other materials.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the contact angle values measured in this study agree with the other previously reported values of water on graphene layers in TEM studies, i.e., in the range of 60° to 90° at the nanoscale. , It is worthwhile to point out that some earlier reported nanoscale contact angles by atomic force microscopy (AFM) are larger than 90°, , which needs to be further clarified in future studies of the intrusive impacts from both TEM and AFM mechanisms in measuring the nanoscale contact angle. Nevertheless, the impact of contact line pinning on nanoscale contact angle is observed in both AFM and TEM studies, and the causes of the pinning can result from both chemical and/or geometrical heterogeneities of 2–10 nm in diameter on the graphene sheets, and a small pinning force between 5 and 70 mN/m can pin the contact line of nanobubbles.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The recent development of liquid cell transmission electron microscopy (LCTEM) has made it possible to observe the dynamic changes of nanomaterials in liquid in real time with high temporal and spatial resolution. Thus far, LCTEM technology has been applied to many fields ranging from materials science to chemistry, physics and biology, such as nanocrystal growth, [21][22][23][24] dissolution, [25][26][27] self-assembly, 28 phase transformation, 29 nanobubble formation, 30,31 electrochemical reactions, 32,33 and bioscience. 34 For the etching of ZnO, recently, Sun et al observed the formation of hillocks on the (0001 ˉ) O-terminated surface of ZnO nanobelts during in situ etching by in situ LCTEM and experimentally demonstrated the micro-mask mechanism.…”
Section: Introductionmentioning
confidence: 99%